A Rights Revolution in Europe? Regulatory and judicial approaches to nondiscrimination in insurance - Deborah Mabbett (London School of Economics and Political Science (LSE), European Institute, 2011)
In a recent decision, the European Court of Justice has ruled that insurers cannot discriminate on grounds of sex in setting premiums or determining benefits. This paper discusses the background to this decision. It asks whether we are seeing a US-style 'rights revolution', fuelled by judicial activism, as suggested by Dobbin et al's hypothesis of 'the strength of weak states' or Kagan and Kelemen's account of 'adversarial legalism'. It is shown that neither of these theories captures the distinctive nature of the ECJ's intervention. An industry-friendly policy was pursued in regulatory venues, but this was overridden by the ECJ's interpretation of the fundamental right of equal treatment. However, it is also shown that the judicial defence of fundamental rights is a weak basis for social policy, and does not foreshadow a revolution in the development of social rights in Europe.
Keywords: 330; Adversarial legalism; discrimination; Gender Directive; insurance; weak state